Biliary tract cancer incidence in the United States—Demographic and temporal variations by anatomic site. Issue 7 (11th April 2013) - Castro, Felipe A.; Koshiol, Jill; Hsing, Ann W.; Devesa, Susan S.
Abstract : We evaluated incidence patterns of biliary tract cancers (gallbladder, extrahepatic bile duct, ampulla of Vater and not otherwise specified) to provide potential insight into the etiology of these cancers. Data were obtained from the population‐based Surveillance, Epidemiology and End Results program. Rates for cases diagnosed during 1992–2009 were calculated by racial/ethnic, gender and age groups. Temporal trends during 1974–2009 and annual percentage changes (APC) during 1992–2009 were estimated. Age‐adjusted rates by site were higher among American Indian/Alaska Natives, Hispanics (white) and Asian/Pacific Islanders (Asian/PI) and lower among whites and blacks. Gallbladder cancer was more common among women in all ethnic groups (female‐to‐male incidence rate ratio [IRR] ranged from 1.24 to 2.86), but bile duct and ampulla of Vater cancers were more common among men (female‐to‐male IRR 0.57 to 0.82). Gallbladder cancer rates declined among all racial/ethnic and gender groups except blacks (APC −0.4% to −3.9%). In contrast, extrahepatic bile duct cancer rates rose significantly in most female racial/ethnic groups; the APCs among whites were 0.8 among females and 1.3 among males, both significant. Rates for ampulla of Vater cancer decreased among Asian/PI females (APC −2.7%) but remained stable for the other groups. In addition to confirming that biliary tract cancer incidence patterns differ by gender and site and that the gallbladder cancer incidence rates have been declining, our study provides novel evidence that extrahepatic bile duct cancer rates are rising. These observations may help guide future etiologic studies. Abstract : What's new? Cancers of the biliary tract are rare but often fatal, and the risk factors for them are not well known. Analysis of data from the U.S. Surveillance, Epidemiology, and End Results (SEER) program revealed elevated rates of biliary tract cancers among American Indian/Alaska Natives, Hispanics, and Asian/Pacific Islanders compared with blacks and whites. Gallbladder cancer rates declined among most ethnic groups, whereas extrahepatic bile duct cancer rates rose, especially among women. These observations suggest that these cancers may differ in their etiology and provide clues for further research.